"I Felt Like a Normal Human Being": Professional DJs' Experiences of the COVID-19 Lockdowns - Marshall, Lee; Whitfield, Martha (Popular music and society, 2024)
The social restrictions prompted by COVID-19 disproportionately impacted creative industries that rely upon live performance as a main source of revenue, including the (electronic) music industry, resulting in widely reported financial hardship experienced by musicians. Based on original interview data, this article offers more nuanced insight into the experiences of professionally well-established EDM DJs. Our data show that while the DJs experienced anxiety and hardships matching those reported elsewhere, many also noted a less reported, more positive, dimension: In forcing a break from work, lockdowns created space to reflect upon the harmful effects of creative working practices and to envisage more fulfilling work-life balances.